Analisis strategi, tantangan dan implementasi penanganan pembiayaan bermasalah (NPF) pada produk pembiayaan mikro syariah di BSI KCP Lumajang S. Parman - Sofiah, Alfiani Farhatus (Maliki Interdisciplinary Journal, 2025)
Sharia microfinance plays a strategic role in empowering the economy of small and medium enterprises, but is vulnerable to the risk of Non-Performing Financing (NPF) due to internal and external factors. This study examines the strategies, challenges, and implementation of NPF management in microfinance products at BSI KCP Lumajang S. Parman. The strategies implemented include a preventive approach through customer selection and feasibility analysis, monitoring, and education; a curative approach in the form of financing restructuring (rescheduling, reconditioning, restructuring) in accordance with the DSN-MUI Fatwa; and a repressive approach as a last resort. Implementation is carried out in a humane and persuasive manner, with a gradual collection mechanism and collaboration with financing guarantee institutions to mitigate risks. The analysis shows that the effectiveness of Sharia microfinance management depends not only on technical banking instruments but also on the synergy between sharia principles, customer empowerment, and protection of the interests of financial institutions.